Congruence and Discrepancy of Interictal and Ictal EEG With MRI Lesions in Pediatric Epilepsies. (November 2020) - Rémi, Jan; Shen, Sophie; Tacke, Moritz; Probst, Philipp; Gerstl, Lucia; Peraud, Aurelia; Kunz, Mathias; Vollmar, Christian; Noachtar, Soheyl; Borggraefe, Ingo
Purpose . To evaluate the congruence or discrepancy of the localization of magnetic resonance imaging (MRI) lesions with interictal epileptiform discharges (IEDs) or epileptic seizure patterns (ESPs) in surface EEG in lesional pediatric epilepsy patients. Methods . We retrospectively analyzed presurgical MRI and video-EEG monitoring findings of patients up to age 18 years. Localization of MRI lesions were compared with ictal and interictal noninvasive EEG findings of patients with frontal, temporal, parietal, or occipital lesions. Results . A total of 71 patients were included. Localization of ESPs showed better congruence with MRI in patients with frontal lesions (n = 21, 77.5%) than in patients with temporal lesions (n = 24; 40.7%) ( P = .009). No significant IED distribution differences between MRI localizations could be found. Conclusions . MRI lesions and EEG findings are rarely fully congruent. Congruence of MRI lesions and ESPs was highest in children with frontal lesions. This is in contrast to adults, in whom temporal lesions showed the highest congruency with the EEG localization of ESP. Lesional pediatric patients should be acknowledged as surgical candidates despite incongruent findings of interictal and ictal surface EEG.